HIGH PRECISION WEIGHING LYSIMETERS FOR EVAPOTRANSPIRATION MEASUREMENTS OF SUGARCANE PRE-SPROUTED PLANTLETS - Libardi,Luís G. P. (2018)
Abstract Sugarcane pre-sprouted plantlets (PSP) production system is an innovative method to enhance crop multiplication rate. Determination of crop evapotranspiration (ETc) is crucial for water requirement identification throughout the plant cycle for irrigation management. ETc can be satisfactorily measured by weighing lysimeters. The objective of the study was to construct and calibrate three low-cost weighing lysimeters to measure ETc of PSP. The built lysimeters had 0.6909 m2 area (1179 mm × 586 mm), with 400 mm depth supported by 3 load cells. Lysimeters calibration showed excellent precision measurements, due to high linear correlation (R2 = 1.0000) between electric signal and equivalent mass, high accuracy, confirmed by mean absolute error between 0.0272 and 0.0382 mm, mean square error between 0.0011 and 0.0024 mm2 and Willmott's index of agreement (d) equal to unit. Maximum hysteresis (0.1951 mm) and hysteresis at full scale (0.4492%) did not compromise the evaluations. Daily ETc measurements showed variation of 0.27 mm among lysimeters and were coincident with daily course of reference evapotranspiration (ETo). The cost of the equipment was low, except for the data acquisition system. Therefore, lysimeters presented low cost and were adequate to measure ETc of PSP in greenhouse-grown.